The Significance of Standardisation and Standardised Management Systems in the Policy of Sustainable Development - Łańcucki , Jerzy (Studia Oeconomica Posnaniensia, 2016)
In a number of initiatives related to the implementation of sustainable development strategy, the economic, social and environmental questions are the leading subjects. One of the tools used in the implementation of the strategy and accordingly sustainable development policy can be standardisation. The study seeks to discuss the elements of sustainable development and the most important international initiatives related to this subject. Thus, particular attention is paid to EU Sustainable Development Strategy, Europe 2020 strategy, and Agenda 2030 for Sustainable Development. Against such a background, the author sets forth the importance and role of standards and standardisation in solving significant social, economic and environmental questions that are the basis for sustainable development policy. The special role of standards related to good management practices is highlighted. These standards apply, among other things, to quality, environment, information and work security, risk, and food safety, and energy as well as activity in the field of social responsibility. Subsequently, the factors and circumstances affecting how effectively the standards are developed and implemented have been described. Conclusively, potential barriers which in the near future may hinder or even prevent the use of standards, especially in case of small and medium-sized enterprises, have been described. Such enterprises have a dominant role in the economies of many European countries.